Heritage and tourism in "the global village" / Priscilla Boniface; P J Fowler - Boniface, Priscilla
International in scope, this book examines both succesful examples of heritage management as well as some failures. It provides the principles which should underpin all heritage developments designed to attract tourism on a major scale.